Beyond Influence: How Influencer Credibility and Self-Congruence Drive Skincare and Bodycare Purchase Intention Among Millenials and Gen Z - Tazkia Prifa Maharani; Daniel Tumpal Hamonangan Aruan (International Journal of Business Studies, 2025)
In today's digital age, beauty influencers play a big role in shaping how people choose skincare and bodycare products. This study looks at how two factors source credibility (how trustworthy an influencer seems) and self-influencer congruence (how similar the influencer feels to the consumer) affect the purchase intentions of Millennials and Gen Z in Indonesia. The research also explores whether parasocial relationships (feelings of closeness with an influencer) and trust help explain this influence. Using survey data from 360 social media users who follow beauty influencers, the study applied statistical analysis (PLS-SEM) to test these relationships. Results show that both credibility and similarity significantly impact purchase intentions—both directly and through trust and parasocial bonds. These psychological connections are key in turning influencer influence into actual buying behavior. This study helps improve our understanding of influencer marketing and gives brands insights on how to create more authentic and effective campaigns by choosing influencers who resonate well with their audience.